Adherence to national guidelines for antiemesis prophylaxis in patients undergoing chemotherapy for lung cancer12. Issue 7 (4th December 2012) - Gomez, Daniel R.; Liao, Kai‐Ping; Giordano, Sharon; Nguyen, Hoang; Smith, Benjamin D.; Elting, Linda S.
Abstract BACKGROUND: Nausea and vomiting (N/V) during chemotherapy can have profound clinical and economic consequences. Effective antiemetic agents are available for prophylaxis, but barriers may prevent their use. For this population‐based study, the authors assessed the rates of antiemetic prophylaxis use, and predictors of such use, among patients who were receiving platinum‐based chemotherapy for lung cancer between 2001 and 2007. METHODS: The authors searched the Texas Cancer Registry–Medicare‐linked database for individuals aged >65 years who received platinum‐based chemotherapy within 12 months after a first diagnosis of lung cancer from 2001 to 2007; and all patients had continuous Medicare Part A and Part B coverage for the same period. Adherence to recommended regimens for N/V prophylaxis (established by the National Comprehensive Cancer Network) was scored as a binary variable (adherent vs nonadherent) and was calculated as the percentages of treated patients receiving each recommended agent within 1 day of beginning chemotherapy. Logistic regression with stepwise selection was used to examine whether patient characteristics influenced adherence. RESULTS: Of 4566 selected patients, adherence rates for the receipt of serotonin antagonists (eg, ondansetron) with dexamethasone were 60% to 90% regardless of whether the chemotherapy agent was considered moderately or highly emetogenic. The receipt of substance‐P antagonists was much less common (<10%) during any period. On multivariate logistic regression modeling, variables that predicted adherence were older age, white race, higher median income, and concurrent radiation therapy. CONCLUSIONS: Recommended use of antiemetics for prophylaxis, especially substance‐P antagonists, during chemotherapy for lung cancer is suboptimal. Factors that were correlated with adherence suggest socioeconomic barriers in the community. Cancer 2013. © 2012 American Cancer Society.